Capillary Desaturation Curves For Evaluating Surfactant Performance By Core Flooding Experiments - Sugihardjo Sugihardjo (Scientific Contributions Oil and Gas, 2009)
Capillary desaturation curves are normally generated in laboratory scale by means of core flooding experiments to evaluate the surfactant formulations for chemical injection in EOR projects. Low tension surfactant solution is the only liquid that could increase the dimensionless capillary number in order of magnitude of 103. Two types of core samples have been used in core flooding experiments to develop capillary desaturation curves, i.e., generic and standard Classhach core samples. In Addition, VS surfactant and additional alcohols are also used in these experiments. The higher the capillary number could generate a lower the residual oil saturation. Moreover, each rock may have a particular capillary desaturation curve depending on the rock properties. Therefore before implementing chemical injection in a pilot scale, capillary desaturation curve should be developed in laboratory to evaluate the surfactant injection performance.